183 Risk of Hypoglycaemia in Older Patients in Residential Care on Oral Hypoglycaemic Medication. (16th September 2019) - Brennan, M; Crowe, A; Tiernan, C; Smith, M; Cogan, L; Purcell, R; Griffin, C; Crowe, M
Abstract: Background: Diabetes mellitus (DM) is common in older patients in residential care(RC) with prevalence ranging from 11-36%.Guidlines(1) on glucose targets to avoid the risk of hypoglycaemia or hyperglycaemia respectively in older people recommend avoiding a fasting glucose on treatment of 6mmol/L or a random glucose level higher than 11.0mmol/L. An HbA1c of 53to 59mmol/mol(7-7.5%) should be aimed for although this may need adjusting in RC and StoppFrail guidelines suggest a target of HbA1c of <8%(64mmol/mol). We assessed the prevalence, drug treatment and glycaemic control in 107 older patients in residential care at two sites in Dublin. Methods: Patients with DM were identified from review of medical notes. Hypoglycaemic treatment whether oral hypoglycemic drugs(OHD) or insulin, capillary blood glucose measurements(CBGM) over the previous 28 day period, HbA1c values and weight change over the previous year respectively were tabulated from patient records. Results: Sixteen patients (15%) aged 66-93 were documented with DM. Eight (50%) were on no hypoglycaemic treatment in whom OHD had been discontinued in 2 patients over the previous 6 months because of risk of hypoglycaemia.. Six patients (38%) were only on OHD, whilst 2 were on insulin. Of the 6 patients on OHD, CABGM were below 6mmol/L in 3 patients (50%) with no values above 11mmol/L. All 3 patients had lost weight ( 2.5-6.8Kg) over the previous year and HbA1c levels were below 53mmol/mol (7%) in all 3 patients. Conclusion: Although our numbers are small, 50% of our patients in residential care on OHD are at risk of hypoglycemia possibly related to weight loss. Reducing or discontinuing their OHD may be appropriate.